Suicide « à la kashinawa ». Le désir de l’au-delà ou la séduction olfactive et auditive par les esprits des morts - Barbara Keifenheim (Journal de la Société des Américanistes)
The Kashinawa’s concept of suicide. Longing for the other world or sensory seduction by the spirits of the deceased. The Kashinawa’s concept of suicide according to which the cause for a voluntary death must be searched for in the olfactory and auditory contact with the spirits of the deceased, raises fundamental questions concerning the process of mediation – specific to every culture – between sensory perception and interpretation. In order to clarify this process in the case of the Kashinawa, this article presents some particularities of the indigenous universe of perception.